الأهمية الاقتصادية لبعض النباتات الطبية والعطرية في المنطقة الساحلية ( نموذج الزعتر الخليلي Khalili thyme ( (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2017)
تعد النباتات الطبية والعطرية (الزعتر الخليلي) من الزراعات الاقتصادية المهمة ، وقد أُدخِلَت إلى الزراعة السورية حديثا" كإحدى الزراعات البديلة ، وخاصة" في المنطقة الساحلية، وقد هدف البحث إلى توضيح الأهمية الاقتصادية لزراعة نبات الزعتر الخليلي في المنطقة الساحلية ، حيث أُجريَت هذه الدراسة على جميع المزارعين الذين تم إحصاؤهم ميدانيا ً في محافظتي طرطوس واللاذقية ، وبلغ عددهم 213 مزارعاً ، بمساحة مزروعة بلغت 565 دونم في عام 2015 . لقد أستخدم في التقويم الاقتصادي لهذه الزراعة مؤشرات الكفاءة الاقتصادية بالاستناد إلى بيانات ومعطيات تم جمعها من منطقة الدراسة . وقد أظهرت الدراسة أن الربح السنوي المحقق من الدونم الواحد من الزعتر الخليلي بلغ نحو 151451.81 ل.س ، و بلغ معامل الربحية بالقياس إلى التكاليف الإنتاجية الأولية نحو 283.64%، أما مؤشر زمن استعادة رأس المال للزعتر الخليلي فكان 2.82 سنة .The medicinal and aromatic plants (thyme Khalili) is one of important economic crops were introduced to the Syrian Agriculture recently "as one of the most important alternative crops, especially" in the coastal region, The goal of research is to clarify the economic importance of agriculture thyme Khalili in the coastal region, This study was conducted on all farmers who were counted on the ground in Tartous and Latakia Governorates, there were 213 farmers ,with planted area reached to 565 acres in 2015.The indicatives of economical feasibility based on data and statements gathered from site of research and relying,were used in the economical evaluation .The study showed that the totally achieved profit per annum from one acre of (thyme khalili) amounted to 151451.81 Syrian Pounds , and profitability coefficient in proportion to the productivity cost has amounted to 283.64%, also the time indicator of capital recovery for (Thyme Khalili) has amounted to 2.82 years.